2017
DOI: 10.1371/journal.pone.0171134
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Mediator Complex Subunit 19 Suppresses the Growth and Invasion of Prostate Cancer Cells

Abstract: Prostate cancer (PCa) is one of the most common cancers in elderly men. Mediator Complex Subunit 19 (Med19) is overexpressed and plays promotional roles in many cancers. However, the roles of Med19 in PCa are still obscure. In this study, by using immunohistochemical staining, we found higher expression level of Med19 in PCa tissues than in adjacent benign prostate tissues. We then knocked down the Med19 expression in PCa cell lines LNCaP and PC3 by using lentivirus siRNA. Cell proliferation, anchor-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Beyond its interaction with ER, MED1 was shown to be essential for the expression of ER target genes and proliferation in breast cancer cells [15, 50]. In line with other studies on the dispensability of MED1, MED1 was only present in about 20% of mediator complexes, with MED1-containing Mediator also enriched for MED19 and MED15, both of which have been implicated in breast cancer, as well as prostate cancer (discussed below) [15, 20, 38, 51, 52]. This indicates that MED19 and MED15 may cooperate with MED1 in breast cancer to promote ER activity.…”
Section: Mediator and Endocrine Cancerssupporting
confidence: 52%
See 3 more Smart Citations
“…Beyond its interaction with ER, MED1 was shown to be essential for the expression of ER target genes and proliferation in breast cancer cells [15, 50]. In line with other studies on the dispensability of MED1, MED1 was only present in about 20% of mediator complexes, with MED1-containing Mediator also enriched for MED19 and MED15, both of which have been implicated in breast cancer, as well as prostate cancer (discussed below) [15, 20, 38, 51, 52]. This indicates that MED19 and MED15 may cooperate with MED1 in breast cancer to promote ER activity.…”
Section: Mediator and Endocrine Cancerssupporting
confidence: 52%
“…Indeed, depletion of MED19 by siRNA reduced the expression of AR target genes in LNCaP-abl cells (androgen-independent prostate cancer cell line), and reduced the proliferation in both LNCaP-abl cells and LNCaP cells (androgen-dependent prostate cancer cell line) [20]. MED19 has also been implicated in the growth of prostate cancer cells in other studies [37, 38]. Although no studies have examined MED19 as an ER co-regulator, it has been demonstrated to play a role in the growth of breast cancer cells, indicating that it may regulate ER signaling [39, 40].…”
Section: Mediator and Nuclear Receptors: Estrogen Receptor Alpha (Ementioning
confidence: 99%
See 2 more Smart Citations
“…29 MED19 downregulation inhibited colony formation, migration, and invasion, as well as cell growth and EMT-related genes such as p27, E-Cadherin, N-Cadherin, vimentin, snail-1 and snail-2 in prostate cancer. 30 Interfering with MED19 induced cell cycle arrest at the G1 phase and prohibited migration in tongue cancer cells. 31 Here, we revealed that MED19 induced the EMT process by activating the Wnt/βcatenin pathway in CRC, providing a possible mechanism by which MED19 affects tumorigenesis and metastasis.…”
mentioning
confidence: 99%